Blaming the victim: Aspects of the Brazilian case - Almeida, Ildeberto Muniz de [UNESP]; Binder, MCP; Fischer, F. M. (Baywood Publ Co Inc, 2000)
This report describes the consequences and some aspects of the origin and development of victim blaming in accident analysis, and some methods for investigating such events, with particular emphasis on the situation in Brazil. In Brazil, the spread of this practice seems to have been helped by several factors. (1) the idea that occupational accidents are simple phenomena with a limited number of causal factors linked to unsafe actions and/or conditions. In the past, the theory of accident proneness had less influence than in other countries. (2) Government regulations that stipulate the hiring of health and safety officers, production of educational material, and preventive campaigns that emphasize the role of the victim's faulty behavior in the origin of an accident. (3) Mandatory implementation of standardized models for accident investigation directed toward searching for a single cause. Usually one conclusion, expressed in terms of unsafe acts or conditions, is formulated so that whoever performs an unsafe act is responsible for the accident. (4) Lack of knowledge, as shown in Brazilian publications on occupational accidents and in the evolution of studies on the nature of accident phenomena and of strategies adopted for their prevention.